Form and Gender of Language Politeness in TikTok Densu Comment Column - Yolanda Rensia Gigik; Nur Lailiyah; Encil Puspitoningrum (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
The purpose of this research is to describe the form of politeness and gender factors on politeness in language in TikTok comments by Denny Sumargo and Mahfud MD. The research method used is the technique of listening and recording, classification, analysis, drawing conclusions, then reporting the results of the study. The type of research used is descriptive qualitative, with a pragmatic approach. The results of this study found 14 data of wisdom maxims, 4 data of generosity maxims, 52 data of praise maxims, 8 data of humility maxims, 7 data of agreement maxims, and 43 data of sympathy maxims, with a total of 128 data. The gender factor in this study was found to be male with a subcategory of internal psychological factors of 4 data, external environmental factors of 9 data. The female gender factor was a subcategory of internal psychological factors of 9 data and external environmental factors of 6 data, so the total was 28 data. In this study, the maxim of praise occupies the most frequently spoken position and the maxim of praise expects the speaker when delivering a speech not to insult, mock or belittle others. Therefore, the maxim of praise is the most frequently found maxim in this study. politeness of language is not only from the form of politeness, but also gender factors, men tend to speak politely by paying attention to external environmental factors in contrast to women who tend to speak in terms of internal psychological factors using feelings.